Potensi Dark Tourism Pasca Bencana di Kawasan Ekonomi Khusus Tanjung Lesung, Provinsi Banten - Faisal, Faisal; Arifin, Djauhar; Utomo, Bambang Sapto; Noerdjmal, Daeng; Kalsum, ER. Ummi (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2020)
On December 23, 2018, a tsunami caused by the eruption of Mount Anak Krakatau in the Sunda Strait hit the coastal areas of Banten and Lampung. There were at least 426 people killed and 7,202 injured and 23 people missing due to this incident. One of the areas affected by this disaster is the Special Economic Zone (KEK) of Tanjung Lesung Tourism, which was officially opened in February 2015. With this incident, the Tourism sector in the area needs to be considered starting from the development and post-disaster plans. This research was conducted to be able to map out how the potential of new tourism due to disasters that can be used as a plan to develop tourist attractions in the region. This research was conducted qualitatively by involving various key informants as sources of data needed such as the head of the Local Tourism Office, coastal community leaders affected by the disaster, affected communities, hotel owners around the disaster area. From the results of these data and used as a source of information to be used as a result of research. The results of this study are how a new potential emerges utilizing the areas of the former disaster and the mystery stories of the disaster.